The Study of Indian Classical Dance in the Hindu Temple Traditions - Balakailasanathasarma, M. (University of Colombo, 2015)
Hinduism is both a way of life and a highly organized social, religious and cultural system. Although it is difficult to define Hinduism precisely, there can be no denial that a true Hindu recognizes consciously or unconsciously, a force or a power outside of man, which is nevertheless in constant relation with him. And this recognition manifests itself in thought, action and in artistic activities. Included in the religion are strands of philosophy, psychology, aesthetics, rituals and mythology that are interrelated in some way. The important base-level texts for understanding the Hindu way of life are the Vedas and Agamas. The ancient scripture of the Vedas and their ancillary, a large corpus of Vedic literature, which are all in Sanskrit, have been considered a great authoritative source for religion, ethics and poetry, and also for the cultural and artistic life of the Hindu (or Indian in a large sense) from very remote times. Then followed the compilation of Saiva and Vaisnava Agamas, formulating the worship of Siva or Visnu as a preferential (istadevata) or family (kuladevata) deity, either at home or in the temple. Both the Vedas and Agamas are not associated with human authorship but considered as revealed by the Supreme Being (apauruseya). This paper examines the Indian classical dance and temple traditions according to the Vedas and Agamas. The paper concludes that that a detailed study of the gestures used in classical dramatic tradition and those in Saiva Agamas will prove very useful in understanding and analyzing their symbolism, purpose and goal.
Keywords: Classical dance, Temple tradition, Siva worship, Textual tradition